LYSOPHOSPHATIDIC ACIDS AND AUTOTAXIN IN RETINAL VEIN OCCLUSION. Issue 12 (December 2016) - Dacheva, Ivanka; Ullmer, Christoph; Ceglowska, Karolina; Nogoceke, Everson; Hartmann, Guido; Müller, Stephan; Rejdak, Robert; Nowomiejska, Katarzyna; Reich, Michael; Nobl, Matthias; Tandogan, Tamer; Kretz, Florian T. A.; et al.
Abstract : Purpose: To analyze the levels of lysophosphatidic acids (LPAs) and autotaxin (ATX) in undiluted vitreous of untreated patients with retinal vein occlusion (RVO). Methods: Sixty-four vitreous samples (40 RVO, 24 controls with idiopathic floaters) were analyzed in this retrospective case series using LC/MS for LPAs 16:0, 18:0, 18:1, 20:4, and ELISA kits or Luminex technology for ATX, angiopoetin-1 (ANG-1), interleukin-6 (IL-6), interleukin-7 (IL-7), interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1), pigment epithelium-derived factor (PEDF), and vascular endothelial growth factor (VEGF). LPA and ATX levels were correlated with the visual acuity, central macular thickness (CMT), average retinal thickness (AvT), vitreal cytokine levels and with each other. Results: Levels of every LPA species tested and ATX were significantly increased in the vitreous fluid from all patients with RVO (total LPAs: 968.0 ± 842.3 nM; ATX: 2.5 ± 1.02 nM) compared with controls (total LPAs: 225.2 ± 292.8 nM, P < 0.0001; ATX: 1.9 ± 1.00 nM, P = 0.005). There were strong positive correlations between the vitreal levels of IL-6, IL-8, MCP-1, VEGF and LPAs. Conclusion: Levels of LPAs and ATX were positively correlated with proinflammatory cytokines and VEGF and might thus play an important role in the development of macular edema secondary to RVO. Abstract : Supplemental Digital Content is Available in the Text.Intravitreal levels of lysophosphatidic acids (LPAs) and autotaxin (ATX) are increased in patients with retinal vein occlusion compared to control patients with idiopathic floaters. Upregulation of LPAs and ATX in the vitreous fluid seems to be associated with the inflammatory and the angiogenetic pathophysiology of macular edema.